Significado sócio-histórico da luta pela jornada de trabalho de 30 horas semanais para o assistente social brasileiro - Silva, Charlene Souza da (2014)
This study has as its object of analysis the socio-historic significance of the struggle for the workweek from 30 hours without salary reduction for Brazilian social worker. The struggle of the working class by the reduction of working hours is a historic battle that looms over the centuries, with aspects of achievements and regressions. The achievements reflect the gradual reduction of journey as a victory for workers in the capital versus labor confrontation. At the same time, if it regresses time that capital finds mechanisms to circumvent the reduction of journey through measures that camouflage the character of implicit exploration, stepping up the pace of work, for example. The social worker, while employed, assumes the position in favor of these class interests, as it is inserted into the working class and subject to the same determinations that reach. In this sense, the present study aimed to grasp the socio- historical significance of the struggle that culminated in the Law 12.317/2010, mainly through the organization of the category and the strategies of mobilization CFESS / CRESS whole process. The above Act amended the Act Regulating the Profession (Law 8.662/93) and included an article that indicates the workload of social workers for 30 hours without salary reduction. The research was qualitative type based on the analysis of literature and documents on the subject now exposed. The literature used traced a historical evolution of labor and forms of exploitation and how this was reflected in the Social Services, emphasizing the need to reduce the workload. Also documents, reports, legal opinions, information from the |Observatory of the 30 o´clock| CFESS and CRESS and judicial decisions relating to the reduction of working hours for social workers were used. Finally, the results showed this achievement as reflected not only in the gain of reduced journey for the category in question, but, in general, showed a reflection of achievement in working class as a way to stand against the heightened exploitation of labor and in favor better conditions of life and work, as well as quality of services, as proposed by the professional ethical-political project . Also, pointed out the challenges that the professional category still faces to overcome other issues that are directly linked to the reduction of the working day.